Changing Water Regime: Remunicipalization in Indonesia under the Global Hegemony of Privatization - Marwa Marwa (Institute of International Studies, 2019)
The research analyzes the emergence of water remunicipalization as counterhegmonic movement under the global hegemony of water privatization in Jakarta, Indonesia. In doing so, the author applies Gramsci’s theoretical framework of “Battle for Hegemony”, in understanding the dialectical relationship between the hegemony of privatization and remunicipalization as its opposing idea within the context of Indonesia’s water regime. Additionally, the author also uses the concept of “militant particularism” of Raymond Williams to explore the organization of remunicipalization as a counterhegemonic bloc. The opposing idea was materialized into diverse and particular struggles against privatization who connect themselves into one counterhegemonic bloc with a universal feature. Local struggles in Jakarta connected themselves under an anti-privatization movement or well known as the Koalisi Masyarakat Melawan Swastanisasi Air Jakarta (KMMSAJ). Later, KMMSAJ linked itself with a global struggle against water privatization with a counterhegemonic idea of remunicipalization. Nevertheless, the universality of remunicipalization does not necessarily eliminate the particularities of each struggle, as the dissemination of the idea and practice is appropriated to Indonesia’s political-economic context. By analyzing the organization of remuncipalization, this article intends to move the tedious discussion of water privatization that has been centralized to moral or legal human rights claims to a more productive discussion that explores an alternative idea.